2022
DOI: 10.3389/fmicb.2021.798476
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Diversity of Rhizosphere Microbiome Recruited From Compost Synergistically Determined by Plant Species and Compost

Abstract: Compost is frequently served as the first reservoir for plants to recruit rhizosphere microbiome when used as growing substrate in the seedling nursery. In the present study, recruitment of rhizosphere microbiome from two composts by tomato, pepper, or maize was addressed by shotgun metagenomics and 16S rRNA amplicon sequencing. The 16S rRNA amplicon sequencing analysis showed that 41% of variation in the rhizosphere bacterial community was explained by compost, in contrast to 23% by plant species. Proteobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…On the other hand, in agricultural soils and the rhizosphere of tomato plants, Chloroflexi was the fourth and fifth phyla represented. Chloroflexi has already been described in the soil and in the rhizosphere of several plant species including tomato [ 23 , 30 , 56 , 57 ]. Although reported in numerous microbiome studies, there is little information on Chloroflexi because, together, Acidobacteria and Planctomycetes require more than 12 weeks to grow and form very small colonies on culture media and are therefore very difficult to isolate [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in agricultural soils and the rhizosphere of tomato plants, Chloroflexi was the fourth and fifth phyla represented. Chloroflexi has already been described in the soil and in the rhizosphere of several plant species including tomato [ 23 , 30 , 56 , 57 ]. Although reported in numerous microbiome studies, there is little information on Chloroflexi because, together, Acidobacteria and Planctomycetes require more than 12 weeks to grow and form very small colonies on culture media and are therefore very difficult to isolate [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strains of Devosia have been isolated from the rhizosphere of Cq and display a high tolerance to salt, where in vitro experiments have demonstrated that this bacteria can improve the osmotic and physiological performance of the Antarctic vascular plants ( Gallardo-Cerda et al, 2018 ). Additionally, this genus is globally abundant in soil and has been found enriched in the rhizospheres of various plants of economic interest ( Delgado-Baquerizo et al, 2018 ; Wang et al, 2022 ). Finally, representative genus Galbitalea has not been obtained from vascular plant rhizospheres; however, several isolates have been obtained from Antarctic lichens ( Noh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The databases used were SILVA, GREENGENES and NCBI. Each read was classified according to the percentage coverage and identity (Wang et al, 2021). METAGENassist was used for performing the comparative genomics of bacterial populations.…”
Section: Methodsmentioning
confidence: 99%